Efektivitas Konseling Kelompok Berbantuan Teknik Problem Solving Untuk Menurunkan Perilaku Membolos Peserta Didik: Effectiveness Of Helpful Groups Of Problem Solving Techniques To Reduce Behavior Of Breaking Students - Elza Elza; Dina Fariza Tryani Syarif (Suluh: Jurnal Bimbingan dan Konseling, 2017)
The purpose of this study was to determine the level of truant behaviour in students and find out the effectiveness of group counselling services assisted by problem-solving methods to decrease missing behaviour in students. The research methodology used is the experiment. The population in this study were two palangkaraya public high school students with sample X SMA Negeri 2 palangkaraya. The results showed that group counselling with practical problem-solving techniques to reduce students' truant behaviour was evidenced by the scale pretest and posttest scores that had been distributed to 8 LA students (148) reduced to 60, EDL (125) reduced to 55, AWN (121) reduced to 73. RFBB (154) reduced to 98, AYS (152) decreased to 131, pns (114) reduced to 57, gesp (132) reduced to 55, and ET (127) reduced to 72 resulting in a decrease in the average pre-test and post- results test. The reduction in the first average was 191.50 to 69.00, with an average decrease of 65.13. So from that group counselling with excellent problem-solving techniques to be applied to the world of education as one form of guidance and counselling services at school.